THE PLACE OF THE SPIRITUAL AND MORAL ENVIRONMENT IN THE FAMILY IN RAISING CHILDREN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article considers the role of the spiritual and moral environment in the family in the upbringing of children, its specific functions. At the same time, the article addresses the issues of educating the younger generation as a mature person.